Meta‐analysis of the prevalence of thermotolerant Campylobacter in food‐producing animals worldwide - Rossler, Eugenia (2019)
The objective of this meta‐analysis was to summarize available information on the prevalence of thermotolerant Campylobacter (TC) in different food‐producing animals worldwide. Databases (i.e., PubMed, ScienceDirect, Scopus) were searched from 1980 to 2017 unrestricted by language. The inclusion criteria were as follows: prevalence or incidence studies, published in peer‐reviewed journals, and they must have reported the total number of animal samples studied and the number of samples that were positive for the presence of TC. When the identification of Campylobacter species was available, this information was included in the analysis. Multilevel random‐effect meta‐analysis models were fitted to estimate mean occurrence rate of TC and to compare them among different factors potentially associated with the outcome. The mean occurrence rate of TC in food‐producing animals was 0.424 (95% CI: 0.394–0.455), and the mean occurrence rate of Campylobacter jejuni and Campylobacter coli were 0.214 and 0.133, respectively. Pigs and poultry showed the highest prevalence of TC; however, there were differences in the prevalence of each Campylobacter species. Campylobacter jejuni was observed in broilers (0.322; 95% CI: 0.273–0.377) and hens (0.395; 95% CI: 0.265–0.542), while C. coli was restricted essentially in pigs (0.553; 95% CI: 0.541–0.650). The prevalence of C. jejuni in intensively bred cattle was higher (0.302; 95% CI: 0.227–0.389) than the prevalence in extensively bred cattle (0.172; 95% CI: 0.119–0.242) while the prevalence of C. coli was similar (0.051; 95% CI: 0.028–0.091 vs. 0.050; 95% CI: 0.027–0.091) in both production systems. Agar with or without blood used for the isolation of TC did not affect the prevalence observed. The method of species identification did not seem to generate differences in the prevalence of Campylobacter species. The prevalence of Campylobacter in primary food production has a strong impact on the entire agri‐food chain. National authorities must monitor the situation with the aim to establish the appropriate risk management measures.